Revisiting Plant Plasma Membrane Lipids in Tobacco: A Focus on Sphingolipids. Issue 1 (30th October 2015) - Cacas, Jean-Luc; Buré, Corinne; Grosjean, Kevin; Gerbeau-Pissot, Patricia; Lherminier, Jeannine; Rombouts, Yoann; Maes, Emmanuel; Bossard, Claire; Gronnier, Julien; Furt, Fabienne; Fouillen, Laetitia; Germain, Véronique; et al.
Abstract : Glycosyl-Inositol-Phosphoryl-Ceramides are major lipids of the plasma membrane and form rafts in the outer leaflet, yet extend into the inner leaflet of the membrane through very long-chain fatty acids to interdigitate across the membrane. Abstract: The lipid composition of plasma membrane (PM ) and the corresponding detergent-insoluble membrane (DIM ) fraction were analyzed with a specific focus on highly polar sphingolipids, so-called glycosyl inositol phosphorylceramides (GIPC s). Using tobacco ( Nicotiana tabacum ) 'Bright Yellow 2' cell suspension and leaves, evidence is provided that GIPC s represent up to 40 mol % of the PM lipids. Comparative analysis of DIM s with the PM showed an enrichment of 2-hydroxylated very-long-chain fatty acid-containing GIPC s and polyglycosylated GIPC s in the DIM s. Purified antibodies raised against these GIPC s were further used for immunogold-electron microscopy strategy, revealing the distribution of polyglycosylated GIPC s in domains of 35 ± 7 nm in the plane of the PM . Biophysical studies also showed strong interactions between GIPC s and sterols and suggested a role for very-long-chain fatty acids in the interdigitation between the two PM -composing monolayers. The ins and outs of lipid asymmetry, raft formation, and interdigitation in plant membrane biology are finally discussed.